Design and Construction of Ion-Selective Electrode of Cetyl Pyridinium Chloride and Study on the Cetyl Pyridinium Chloride Micellization in Environmental Conditions - Keshavarz, M.; Nasirian, A. (Asian Journal of Chemistry, 2012)
The use of the ion-selective electrodes in the study of equilibrium properties of aqueous surfactant solutions has received much attention for their low equipment costs and the availability of construction materials. In this paper, a silver wire-coated selective electrode for cetyl pyridinium chloride which is more stable and sensitive than the previous ones was constructed and implemented for characterization of micelle solutions of cetyl pyridinium chloride in various experimental conditions. The values of critical micelle concentration (CMC) at various conditions with different temperatures and alcohol percentages have been interpreted and effective influencing factors on the structural stability of micelle were also investigated. The results revealed critical micelle concentration changes with respect to these factors. The critical micelle concentration changes at various temperatures indicated that the most important factors in micelle formation are entropy and enthalpy. This study marked the outstanding role of hydrophobic forces in the micelle formation process with respect to electrostatic interaction.